2014
DOI: 10.1177/0363546514538394
|View full text |Cite
|
Sign up to set email alerts
|

All-Inside Meniscal Repair Devices Compared With Their Matched Inside-Out Vertical Mattress Suture Repair

Abstract: Eight to 10 weeks of rehabilitation might not pose a problem for all repairs in this worst-case scenario.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
25
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
4
4
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 32 publications
(25 citation statements)
references
References 40 publications
0
25
0
Order By: Relevance
“…The molded anchor implants along with the suture provide compression across the tear in the meniscus to close the meniscal tear tightly and promote meniscal healing. Biomechanical studies have shown [32] that all-inside meniscal repair and inside-out meniscal repair can achieve similar biomechanical properties after up to 10,000 cycles of loading.…”
Section: Discussionmentioning
confidence: 99%
“…The molded anchor implants along with the suture provide compression across the tear in the meniscus to close the meniscal tear tightly and promote meniscal healing. Biomechanical studies have shown [32] that all-inside meniscal repair and inside-out meniscal repair can achieve similar biomechanical properties after up to 10,000 cycles of loading.…”
Section: Discussionmentioning
confidence: 99%
“…The OMNISPAN™ the suture provide compression across the tear in the meniscus to close the meniscal tear tightly and promote meniscal healing. The biomechanical studies have shown [29] that the all-inside meniscal repair and inside-out meniscal repair can achieve similar biomechanical properties after up to 10,000 cycles of loading.…”
Section: Discussionmentioning
confidence: 99%
“…A combination of suture techniques and implants might be a treatment option in posterior meniscal lesions 10 . The inside-out repair with all-inside meniscal devices shows comparable biomechanical properties compared with inside-out suture repair in cyclic loading 47 . However, meniscal repair constructs are also exposed to shear forces parallel to the circumferential meniscal fibers during healing, particularly in the midportion of the meniscus (Fig.…”
Section: Meniscal Suture Techniques and Their Biomechanical Consideramentioning
confidence: 91%